Virtual flipped classroom approach for english language teaching: english instructors’ views on the challenges - Othman, Khairunnisa; Ismail, Sheikh Ahmad; Abd Rahman, Siti Fatimah; Mahmud, Nurul Hannan (Universiti Teknologi MARA, 2024)
The implementation of Virtual Flipped Classroom (VFC) approach has gained increasing attention in the field of English Language Teaching. This is due to its potential to enhance learners’ engagement and language acquisition. The present research explores the English language instructors’ perspectives regarding the challenges they face when adopting VFC approach in their teaching practices. Data was collected using a qualitative research design through a semi-structured interview with a purposive sample of four experienced English instructors from one of the public universities in Sepang, Malaysia. Thematic analysis was employed to identify and analyze the emerging themes from the interview transcripts. The findings indicate that English instructors encountered several challenges when implementing VFC approach. Instructors’ responsibilities such as course material preparation and giving personalized feedbacks to learners hinder the seamless delivery of virtual English lessons. Secondly, the instructors faced difficulties in ensuring active engagement and interaction in the virtual environment, which requires innovative instructional strategies and attention to the design of learning materials. Future research should focus on the best practices and solutions to ensure VFC can be implemented in a more comprehensive manner. Also, exploring VFC pedagogical approaches for different English language skills: receptive and productive skills, and across different languages, is needed for the literature of Virtual Flipped Classroom, a new instructional approach for English Language Teaching and Learning.